(untitled) - Rasmussen, Mark David (New York, NY, 2002)
After theory and the new historicism, what might a self-conscious turn to formal analysis in Renaissance literary studies look like today? The essays address this question from a variety of critical perspectives, embodying a renewed engagement with questions of form.
Keywords: English literature,Literary form,Literary form,Renaissance; History and criticism,History,History,England; Early modern, 1500-1700,16th century,17th century